Algebraic identification and estimation methods in feedback control systems - Sira Ramírez, Hebertt J. (Chichester, West Sussex, United Kingdom : John Wiley & Sons Inc., 2014)
"Presents a model-based algebraic approach to on-line parameter and state estimation in uncertain dynamic feedback control systemsAlgebraic Identification and Estimation Methods in Feedback Control Systems presents the model-based algebraic approach to on-line parameter and state estimation in uncertain dynamic feedback control systems. This approach evades the mathematical intricacies of the traditional stochastic approach, proposing a direct model-based scheme with several, easy to implement, computational advantages. This book contains many illustrative, tutorial style, developed examples of the recently introduced algebraic approach for parameter and state estimation in a variety of physical systems of continuous, and discrete, nature. The developments include some laboratory experimental results in several areas related to mechatronics systems. The reader, with an engineering level mathematical background and through the many expository examples, will be able to master the use and understand the consequences of the highly theoretical differential algebraic viewpoint in control systems theory"--
"Algebraic Identification and Estimation Methods in Feedback Control Systems presents the model-based algebraic approach to on-line parameter and state estimation in uncertain dynamic feedback control systems"--
4.2.3 An Introductory Example4.2.4 Samuelson's Model of the National Economy; 4.2.5 Heating of a Slab from Two Boundary Points; 4.2.6 An Exact Backward Shift Reconstructor; 4.3 A Nonlinear Filtering Scheme; 4.3.1 Hénon System; 4.3.2 A Hard Disk Drive; 4.3.3 The Visual Servo Tracking Problem; 4.3.4 A Shape Control Problem in a Rolling Mill; 4.3.5 Algebraic Frequency Identification of a Sinusoidal Signal by Means of Exact Discretization; 4.4 Algebraic Identification in Fast-Sampled Linear Systems; 4.4.1 The Delta-Operator Approach: A Theoretical Framework; 4.4.2 Delta-Transform Properties.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Feedback control systems -- Mathematical models; Control theory -- Mathematics; Differential algebra; Control theory -- Mathematics; Differential algebra; Feedback control systems -- Mathematical models; Technology and engineering; TECHNOLOGY & ENGINEERING -- Mechanical; Electronic books